2022
DOI: 10.1021/acs.langmuir.2c01855
|View full text |Cite
|
Sign up to set email alerts
|

Durable 3D Porous Superhydrophobic Composites for Versatile Emulsion Separation in Multiple Environments

Abstract: Polydopamine as a multifunctional biomimetic polymer with nonselective strong adhesion properties has become a hot research topic in recent years. However, there are a few reports on the durable and effective emulsion separation of polydopamine composites from other materials. Therefore, it is necessary to construct durable polydopamine composites to achieve selective adsorption of materials. In this work, polypyrrole (PPy)-PDA was obtained on sponges by an in situ polymerization reaction, followed by the atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Figure d displays the FT-IR spectra of each component utilized to create the P-CP composite membrane. The deformation vibration of Si–CH 3 in PDMS is represented by the peak that emerges at 794 cm –1 . The characteristic −OH peaks of MFC appeared at wavelengths 1070, 1100, and 1150 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure d displays the FT-IR spectra of each component utilized to create the P-CP composite membrane. The deformation vibration of Si–CH 3 in PDMS is represented by the peak that emerges at 794 cm –1 . The characteristic −OH peaks of MFC appeared at wavelengths 1070, 1100, and 1150 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, compared with common preparation methods, this novel membrane (defined as P-CP) was prepared in bulk, over a large area, and at low cost by using a simple preparation method. It is well-known that PPy has been extensively applied due to its good electrical conductivity, thermal stability, and non-toxicity. We found that many previous works had been focused on PPy-modified membrane materials or sponge materials for oil–water separation. For example, Li et al constructed a Joule/solar-heated copper foam for efficient all-weather recovery of viscous crude oil .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, bioinspired superwetting materials have attracted extensive attention and have been used to treat various oily wastewater. , So far, various methods including femtosecond laser etching, chemical modification, electrodeposition, spray coating, chemical vapor deposition, hydrothermal synthesis, and electrospinning have been explored to fabricate superwetting materials. The membranes fabricated with the electrospinning method have attracted much attention due to their simple structure, high porosity, large specific surface area, and high permeability. , In this regard, Zhang et al prepared a bioinspired superhydrophobic/superoleophilic membrane via electrospinning technology, in which SiO 2 (silicon dioxide) nanoparticles imitated the hydrophobic biowax and polycaprolactone (PCL) porous microspheres imitated the surface nanoprotrusions of a lotus leaf. This membrane was able to separate various oil–water mixtures efficiently and showed excellent recyclability .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many methods about oil removal have been fully investigated, such as emulsion breaking technology, 6,7 heat treatment technology, 8 and supercritical fluid extraction technology. 9 Heat treatment technology can be used in practical applications owing to its low cost, but one of its major disadvantages is the serious emulsification easily generated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, many methods about oil removal have been fully investigated, such as emulsion breaking technology, , heat treatment technology, and supercritical fluid extraction technology . Heat treatment technology can be used in practical applications owing to its low cost, but one of its major disadvantages is the serious emulsification easily generated. , This extraction technique with simple operation and high efficiency is widely employed, while the high cost and toxicity of some extractants limit its application. , Recently, the application of microemulsion extraction technology in oil removal is regarded as a very promising approach. Microemulsions are stable and transparent mixtures of water, oil, surfactants, and cosurfactants with an average diameter of roughly 1 to 100 nm. , Hernandez et al evaluated the removal of crude oil residues from sandy soils by microemulsions.…”
Section: Introductionmentioning
confidence: 99%